Peran Kepemimpinan Kepala Sekolah dalam Meningkatkan Kualitas Peserta didik di SDN Martapuro 2 Kabupaten Pasuruan - Nurilatul Rahmah Yahdiyani; Ani Roisatul Muna; Septi Nurjanah; Sri wahyuni (Universitas Muhammadiyah Enrekang, 2020)
A leader is very important in achieving the success and goals of an organization, as well as the principal who has an important role in achieving educational and learning goals. In leading school principals must have professionalism in order to achieve educational goals, therefore school principals must play a role in the planning, supervision, etc. Improving the quality of schools is one of the goals to be achieved, so to improve the quality of the institution itself the principal must be able to foster and direct teachers to work professionally in order to improve the quality of students. This study aims to determine the efforts or strategies of school principals in improving the quality of students in SDN Martopuro 2 Pasuruan Regency. The research approach used is qualitative research with data collection techniques in the form of direct interviews with related speakers, namely the principal of SDN Martapuro 2, Pasuruan Regency. The results show that the principal acts as a manager, innovator, motivator by carrying out several efforts in improving the quality of students in SDN Martapuro 2 is trying to realize what is the vision and mission of the school, realizing active, effective and efficient learning, arousing interest and motivation student learning and trying to improve the character and moral values ​​of students.